2008
DOI: 10.1021/bi7023699
|View full text |Cite
|
Sign up to set email alerts
|

Effector-Induced Structural Fluctuation Regulates the Ligand Affinity of an Allosteric Protein: Binding of Inositol Hexaphosphate Has Distinct Dynamic Consequences for the T and R States of Hemoglobin

Abstract: The present study reports distinct dynamic consequences for the T-and R-states of human normal adult hemoglobin (Hb A) due to the binding of a heterotropic allosteric effector, inositol hexaphosphate (IHP). A nuclear magnetic resonance (NMR) technique based on modified transverse relaxation optimized spectroscopy (TROSY) has been used to investigate the effect of conformational exchange of Hb A in both deoxy and CO forms, in the absence and presence of IHP, at 14.1 and 21.1 T, and at 37 °C. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 55 publications
3
64
0
Order By: Relevance
“…74,81,90,95 (ii) RDC measurements for HbCO A and a low oxygen-affinity mutant Hb, rHb (αV96W), in the absence and presence of IHP, have confirmed that the transition pathway 69-70 from the unliganded to the liganded state of hemoglobin is likely T → R → R2. (iii) Allosteric effectors, e.g., IHP, alter both the tertiary and quaternary structure of deoxy- and CO-Hb as well as the dynamics of the Hb molecule, thus affecting its ligand affinity.…”
Section: Dynamic and Structural Basis Of Hemoglobin Allosterymentioning
confidence: 85%
See 3 more Smart Citations
“…74,81,90,95 (ii) RDC measurements for HbCO A and a low oxygen-affinity mutant Hb, rHb (αV96W), in the absence and presence of IHP, have confirmed that the transition pathway 69-70 from the unliganded to the liganded state of hemoglobin is likely T → R → R2. (iii) Allosteric effectors, e.g., IHP, alter both the tertiary and quaternary structure of deoxy- and CO-Hb as well as the dynamics of the Hb molecule, thus affecting its ligand affinity.…”
Section: Dynamic and Structural Basis Of Hemoglobin Allosterymentioning
confidence: 85%
“…The conformational exchange described here is consistent with the results from our backbone relaxation study, i.e., the IHP-induced conformational exchange has been detected in three regions, namely, the α 1 β 2 interface, heme pockets, and the presently putative IHP-binding sites. 90 Localized conformational exchange in the α 1 β 2 interface was also detected early on for the indole NH group of β37Trp in HbCO A in the presence of IHP. 95 …”
Section: Dynamicsmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, the binding of BZF or IHP to CO-Hb complex decreases the CO association rate approximately four or eight times, respectively (Marden et al, 1990), and decreases the affinity of R state deoxy-Hb for oxygen . Coletta et al (1999a) have reported the α-and β-chain (Song et al, 2008).…”
Section: Discussionmentioning
confidence: 99%